2008
DOI: 10.1002/poc.1392
|View full text |Cite
|
Sign up to set email alerts
|

The use of XPS spectra for the study of reaction mechanisms: the atom inventory method

Abstract: X‐ray photoelectron spectroscopy (XPS) allows the analysis of the surface atomic composition of a solid and can be used for mechanistic studies of solid–gas and solid–liquid reactions. The change of atomic composition of a surface after a reaction can be calculated considering hypothetical mechanisms based on the known reactivity of the organic moieties bound to the solid surface. Atom inventory of the elements involved in the reactions was used to quantify the components of the XPS spectrum after the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…The S2p region showed a total initial content of 0.74 at% that increased to 5.49 at% after the reaction. The reactions that were considered to calculate the element composition of the spectrum by atom inventory are shown at the bottom of Table (reactions 1 to 5) and are detailed in Scheme .…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The S2p region showed a total initial content of 0.74 at% that increased to 5.49 at% after the reaction. The reactions that were considered to calculate the element composition of the spectrum by atom inventory are shown at the bottom of Table (reactions 1 to 5) and are detailed in Scheme .…”
Section: Resultsmentioning
confidence: 78%
“…The initial spectra and the spectra calculated through the series of reactions using the atom inventory method, were used to postulate the mechanisms involved.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XPS spectrum of the sample obtained is presented in Table 1 with the composition calculated using the atom inventory method. [7] The spectrum was calculated considering the internal interconversion of the SO 2 reduction intermediates (reaction 1) followed by sulfur elimination from the matrix (reaction 2) ( Table 1). No decarboxylation occurred at this temperature during the interconversion between the intermediates and the C/O ratio stays constant.…”
Section: Resultsmentioning
confidence: 99%
“…The reactivities of several carbons modified with SO 2 , including MPGO and nanotubes, with respect to the basic hydrolysis, thiolysis, aminolysis, reaction with alkyl halides, and photolysis of phenylalanine and t-butanol [18][19][20] have already been studied. XPS spectra after the reaction calculated by the atom inventory method, [7] assuming reactions already described in the literature, showed that thiol and t-butanol moieties were inserted via oxidized intermediates, while in aminolysis, only the non-oxidized intermediate was involved. These differences in reactivity would allow a selective functionalization of carbon particles.…”
Section: Introductionmentioning
confidence: 99%